Generalized homotopy in generalized topological spaces - Khalil Bashier, Assakta (The Libyan Journal of Science, 2022)
We extend the notion of homotopy between topological spaces to the setting of generalized topological spaces in the sense of Csaszar. We introduce the new notion of generalized homotopy ((u, )-homotopy) between generalized topological spaces and study some of its basic properties.